TINGKAT PENGETAHUAN ORANG TUA (IBU) TENTANG MAKANAN KARIOGENIK DENGAN KEJADIAN KARIES GIGI PADA SISWA-SISWI KELAS III DI SDN 060971 MEDAN - rosdiana tiurlan simare-mare (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2016)
Carcinogenic food is a type of food which cause the incidence of caries. The type of food which can cause the incidence of caries is sweet food which contains a lot of sugar or sucrose. Most children like sweet and sticky food which is one of the causes of the incidence of caries. The research used descriptive survey method with 35 parents and 35 students as the samples. It was aimed to find out the level of knowledge of parents (mothers) in carcinogenic food with the incidence of caries in grade III student of SDN 060971, Medan, in 2016. It was conducted in june , 2016. Primary data were gathered by conducting direct examination and secondary data were obtained from questionnaires. The results of the research showed that 30 respondent (85,7%) had good knowledge of carcinogenic food and the incidenci caries, 3 respondent (8,6%) had moderate knowledge, and 2 respondent (5,7%) had bad knowledge . the result of the research concerning caries of milk teeth showed that the amount def-t was 91 and the mean def-t was 2,6. The result of the reseach concerning the status of caries of permanent teeth showed that amount of DMFT was 75 and the mean DMF-T was 2,14. The concution was that parents (mothers) had good knowledge of SDN 060971, Medan , was bad or surpassed the target of ? 2.